High-Efficiency Continuous Wave 16 W–7.5 GHz Power Amplifier With a GaN Transistor in Plastic Packaging - Alireza Sadeghi-Fard; Sayyed-Hossein Javid-Hosseini; Vahid Nayyeri; Paolo Colantonio (IEEE Access)
This paper presents an alternative solution for higher frequency power amplifier design. Using a plastic-packaged GaN transistor and high-efficiency design techniques, a power amplifier for the space-to-earth satellite was designed and fabricated. The proposed design approach relies on determining an appropriate design space for the matching networks, defined by identifying optimal power and efficiency contours derived from source/load-pull techniques. The fabricated amplifier achieved in continuous wave (CW) a saturated output power of 41.7–42.4 dBm in the entire frequency band of 7.25–7.85 GHz while maintaining a drain efficiency of 35–39 %. Thermal simulations and measurements demonstrate stable and safe operating conditions in CW operation.